2009
DOI: 10.1002/art.24754
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of interleukin‐7 receptor in inflamed joints mediates interleukin‐7–induced immune activation in rheumatoid arthritis

Abstract: Objective. To evaluate the expression and functional ability of the high-affinity interleukin-7 receptor (IL-7R␣) in patients with rheumatoid arthritis (RA).Methods. Expression of IL-7R␣ and IL-7 was determined in synovial tissue from RA patients and was compared with that in synovial tissue from patients with undifferentiated arthritis (UA) and osteoarthritis (OA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 38 publications
7
50
1
Order By: Relevance
“…By microarray analysis, we identified the IL-7R gene as one of the most highly altered genes in RA synovial fluid macrophages (5-fold increase compared with normal macrophages; P ϭ 1.10 ϫ 10 Ϫ8 ). Other investigators using microarray analysis demonstrated a 4.7-fold increase in the expression of IL7R in the synovial tissue of patients with RA compared with that in the synovial tissue of patients with systemic lupus erythematosus or osteoarthritis (1), which is also consistent with the findings reported by Hartgring et al (2). Because macrophages in the synovial fluid originate from RA synovial tissue, expression of IL-7R was determined in RA compared with normal synovial tissue.…”
Section: To the Editorsupporting
confidence: 84%
See 1 more Smart Citation
“…By microarray analysis, we identified the IL-7R gene as one of the most highly altered genes in RA synovial fluid macrophages (5-fold increase compared with normal macrophages; P ϭ 1.10 ϫ 10 Ϫ8 ). Other investigators using microarray analysis demonstrated a 4.7-fold increase in the expression of IL7R in the synovial tissue of patients with RA compared with that in the synovial tissue of patients with systemic lupus erythematosus or osteoarthritis (1), which is also consistent with the findings reported by Hartgring et al (2). Because macrophages in the synovial fluid originate from RA synovial tissue, expression of IL-7R was determined in RA compared with normal synovial tissue.…”
Section: To the Editorsupporting
confidence: 84%
“…We read with interest the report by Pickens et al (1), in which they documented increased expression of interleukin-7 (IL-7) and IL-7 receptor (IL-7R␣) in the synovial tissue of patients with rheumatoid arthritis (RA), thereby supporting the findings of previous studies (2,3). In addition, they demonstrated increased coexpression of IL-7 and IL-7R␣ in the circulating monocytes, synovial fluid macrophages, endothelial cells, and fibroblasts of patients with RA compared with healthy control subjects.…”
Section: To the Editorsupporting
confidence: 77%
“…For example, IL-7Ra expression by lymphoid cells in the joint in rheumatoid arthritis patients is increased compared with osteoarthritis patients (49). Treatment response to methotrexate in rheumatoid arthritis patients correlated with decreased IL-7 serum level, but not with TNF-a levels (50).…”
Section: Discussionmentioning
confidence: 98%
“…Another interpretation of the different findings in Caucasians and Africans could be that our initial findings in the Caucasian cohort may not have been related to levels of sIL-7Ra but could have been due to other SNPs in LD with rs6897932, which may have had an influence on CD4 T-cell recovery. This is of course possible but we believe this is less likely given the clear relationship in vitro between sIL-7Ra levels and IL-7 function in primary T-cells, 36,37 and that sIL-7Ra has a binding affinity similar to membrane-bound IL-7Ra on T-cells. 38 Finding the opposite association between genotype and phenotype in replicate genetic studies has been described previously as a 'flip-flop phenomenon,' 39 and is commonly reported in genetic association studies across different ethnic groups.…”
Section: Discussionmentioning
confidence: 99%